Přístup singles k seznamování v digitální době - Šetinová, Markéta; Kalinová, Eliška (Lidé města, 2024)
This text focuses on the attitudes of single young people on dating. As a part of this study, twenty interviews with respondents between the ages of 20 and 40 – who loosely represent the generation of millennials, that is, those who grew up with technology and who are taking advantage of the globalized world – were analysed using thematic analysis. Using semi-structured interviews, this text critically examines how young singles think about mate selection, where they meet prospective partners, and their reasons for choosing online dating sites. Another area of interest are the barriers to using dating services and the behaviour of singles on dating sites, especially regarding sex dynamics. The results correspond to previous findings from studies conducted abroad. On the one hand, a liberal, individualized approach to relationships is evident among the respondents: they focus on their needs within a relationship, they want a partner with whom they will develop mutually, they have a desire to experiment with different relationship forms, and they quickly adopt new technologies when dating. On the other hand, they are still attracted to the traditional ideal of marriage and family, the expectations of men and women within a relationship differ, and even in modern online dating, traditional sex patterns appear.